The Effect of University Students’ Perceptions of Coronavirus Anxiety on Their Level of Socialization Through Sports - Sahin, Ahmet; Acar, Gokhan; Sahin, Filiz (Progress in Nutrition, 2022)
Study Objectives: This study aimed to examine the effects of university students’ perceptions of coronavirus anxiety on their level of socialization through sports. For this purpose, a total of 284 students, 205 male, 79 female, students studying at Mehmet Akif Ersoy University Faculty of Sports Sciences in the fall semester of the 2021-2022 academic year constitute the universe of the study. Among the students who constitute the population of the study, 114 students are studying in the Department of Physical Education and Sports Teaching, 8 in the Department of Sports Management, and 162 in the Department of Coaching Education. Methods: In the analysis of the study data, descriptive statistics such as mean, standard deviation, frequency, and percentage values were examined. Test of normality was examined first to determine whether parametric analyzes will be performed. Results: When the socialization levels of university students through sports were evaluated according to age groups, the level of socialization through sports of students in the 21-22 age group is significantly higher than the level of socialization through sports of the students in the 18-22 age group. It was determined that the levels of socialization through sports of the students studying in the coaching education department were significantly higher than the levels of socialization through sports of the students studying in the physical education and sports teaching department. Conclusion: In the correlation analysis, it was determined that there was a very weak negative correlation between the coronavirus anxiety and the sports and socialization.